AIK KOPI’S MARKETING STRATEGY TO INCREASE CUSTOMER SATISFACTION - Anisah, Nur; A, Gun Sukirman (Jurnal Insani, 2023)
This study aims to describe or explain the marketing communication strategies employed by Aik Kopi in an effort to improve customer satisfaction. The method used in this study is a qualitative descriptive research method, employing purposive sampling to select four competent informants capable of answering all questions in this study. Data in this study were obtained from interviews with selected informants, written data, and researcher observations. To enhance customer satisfaction, the owner of Aik Kopi employs an integrated marketing communication (IMC) strategy. The results of this study indicate that the integrated marketing communication strategies implemented by Aik Kopi include advertising, direct sales, sales promotions, public relations activities, and publicity by supporting small and medium enterprises (SMEs) and employing local residents near the Aik Kopi café, as well as humanitarian activities such as fundraising and providing assistance to orphaned children. Meanwhile, to enhance customer satisfaction, Aik Kopi implements communication strategies such as improving coffee product quality, providing friendly service, and creating a comfortable ambiance.